Relación entre el impuesto sobre el valor agregado y el crecimiento en las empresas del sector industrial del Ecuador (2015-2016) - Terán Solórzano, Joselyn Enma (2022)
The purpose of this research project was to analyze the relationship between the value added tax and growth in micro, small and medium-sized enterprises (MiPyMes) in the manufacturing sector in the period 2016. For this reason, the investigation took into account the variation that existed in the growth rates of MiPyMes in 2016 due to the VAT increase of two percentage points compared to the tax of the previous year. Considering the context, it was proposed to apply an econometric model based on multiple linear regression where the orthogonal transformation by principal components was carried out, which allowed knowing the growth taking into account two dimensions: the growth rate of the assets and the income of the companies. Based on the analysis carried out, the averages of the variables showed an apparently positive relationship between the value added tax and the growth of MiPyMes, but when applying the model it turned out that the increase is statistically significant, that is, it does produce significant changes. about business growth. The research provides necessary information so that micro, small and medium-sized companies know the influence of the VAT increase in relation to the growth of their income and assets, so they can create a contingency plan where they foresee strategies in different scenarios against a possible increase in the VAT rate. In order to carry out the investigation, it was necessary to know the different theories about the variables mentioned in an epistemic way, it should be noted that the collection of the tax did not turn out to be the company's own income since it was focused on generating funds for the government to solve damages caused by the earthquake. in Manabí and its surroundings, but the companies did not obtain any additional profitability benefit by being collection intermediaries, on the contrary, they had to reduce the added value of their products, in addition to the fact that the companies were already in debt, their level of indebtedness grew even more due to the increase in the VAT rate and showed fictitious liquidity in their balance sheets.